Molecular Mechanism of Palmitic Acid on Myocardial Contractility in Hypertensive Rats and Its Relationship with Neural Nitric Oxide Synthase Protein in Cardiomyocytes - Tan, Haibo (Biomed Res Int, 2021)
OBJECTIVE: It is aimed at investigating the mechanism of palmitic acid (PA) on myocardial contractility in hypertensive rats and its relationship with myocardial neural nitric oxide synthase (nNOS) protein. METHODS: The rats were randomly divided into sham operation group and hypertensive group, with thirty rats in each group, to prepare angiotensin II-induced hypertensive model rats. The blood pressure of rats was measured by the multianimal multichannel tail cuff noninvasive blood pressure system of Kent Coda, USA. The Ionoptix single-cell contraction detection system was used to detect myocardial cells. ATP level of left ventricular cardiomyocytes was determined by luminescence method, and protein was measured by Western blot. RESULTS: Compared with the sham group, systolic blood pressure and diastolic blood pressure were increased in the hypertensive group over 4 weeks; PA increased the contractility of left ventricular cardiomyocytes in normal rats, but not in hypertensive rats, and PA increased the intracellular ATP level of rats in the sham group but not in the hypertension group. In the hypertension group, the expression of nNOS in the cardiomyocytes was significantly increased, and specific nNOS inhibitor S-methyl-L-thiocitrulline (SMTC) was found to restore the positive inotropic effect of PA in the myocardium of the hypertension group. PA was supplemented after using CPT-1 inhibitor etomoxir (ETO); it was found that ETO inhibited the positive inotropic effect of PA on left ventricular cardiomyocytes in the sham group, and PA was supplemented after using SMTC and ETO, it was found that SMTC + ETO could inhibit the positive inotropic effect of PA on left ventricular cardiomyocytes in myocardium of hypertensive rats. CONCLUSION: PA could increase the contractility of healthy cardiomyocytes, but had no obvious positive effect on the cardiomyocytes of hypertensive rats, PA enhanced the contractility of cardiomyocytes by increasing ATP level in them, and the inhibitory effect of PA on myocardial contractility in hypertensive rats may be related to the increased nNOS and CPT-1 in cardiomyocytes.